A case of cardiac myxoma with obstructive symptoms: Recognizing key early signs for improved diagnosis - Filano, Marco; Kuhn, Corinna Maria; Zhao, Zihan; Laukkanen, Noora Julia; Rahimah, Anna Fuji; Karolina, Wella; Prasetya, Indra; Rohman, Mohammad Saifur (Universitas Brawijaya, 2026)
Background: LA myxoma is the most common primary cardiac tumor, often presenting with obstructive symptoms when the tumor prolapses into the mitral valve during diastole. On the other hand, rheumatic MS leads to fixed obstruction of the mitral valve. The coexistence of both conditions is extremely rare and can exacerbate the severity of mitral inflow obstruction. Early recognition of this dual pathology through careful clinical evaluation and echocardiographic assessment is crucial for timely and effective management. Case Presentations: A 66-year-old female patient presented with progressive dyspnea. Transthoracic echocardiography detected a mobile mass in the left atrium and later identified it as a cardiac myxoma. Further evaluation revealed severe rheumatic mitral stenosis (MS) with a mitral valve area (MVA) measured by planimetry at 1.23 cm², restricting the mass from slipping into the left ventricle during the diastolic phase. Based on the conference decision, tumor resection was performed, and the histopathological examination revealed a left atrial (LA) myxoma. The dual obstruction caused by mitral valve stenosis and a left atrial myxoma resulted in life-threatening symptoms due to diastolic obstruction of mitral inflow. In isolated LA myxoma, the tumor pushes into the mitral valve opening during the heart's relaxation phase, blocking blood flow from the left atrium to the left ventricle and raising pressure in the atrium and lungs. When significant MS is present, the narrowed valve further worsens this obstruction, leading to higher atrial pressure and more severe heart failure symptoms. Both conditions commonly present with early symptoms such as exertional dyspnea, palpitations, signs of heart failure like edema and pulmonary crackles, diastolic murmur, and sometimes syncope caused by reduced cardiac output. Conclusions: This case highlights the critical importance of identifying early obstructive symptoms indicative of cardiac myxoma. Timely identification of these clinical manifestations can facilitate earlier diagnosis, improve patient outcomes, and prevent potentially fatal complications.